Danionella dracula, an escape from the cypriniform Bauplan via developmental truncation?. (20th November 2015) - Britz, Ralf; Conway, Kevin W.
ABSTRACT: We provide a detailed account of the osteology of the miniature Asian freshwater cyprinid fish Danionella dracula . The skeleton of D. dracula shows a high degree of developmental truncation when compared to most other cyprinids, including its close relative the zebrafish Danio rerio . Sixty‐one bones, parts thereof or cartilages present in most other cyprinids are missing in D. dracula . This impressive organism‐wide case of progenesis renders it one of the most developmentally truncated bony fishes or even vertebrates. Danionella dracula lacks six of the eight unique synapomorphies that define the order Cypriniformes and has, thus, departed from the cypriniform Bauplan more dramatically than any other member of this group. This escape from one of the most successful Baupläne among bony fishes may have been facilitated by the organism‐wide progenesis encountered in D. dracula . By returning in its skeletal structure to the early developmental condition of other cypriniforms, D. dracula may have managed to overcome the evolutionary constraints associated with this Bauplan and opened up new evolutionary avenues that enabled it to evolve a number of striking morphological novelties, including its tooth‐like odontoid processes and a complex drumming apparatus. J. Morphol. 277:147–166, 2016. © 2015 Wiley Periodicals, Inc.